Measurement of the Radon Concentration and Annual Effective Dose in Malva sylvestris (Khabbaz) Plant Used in Traditional Medicine and Food - Mohammed et al. (Baghdad Science Journal, 2020)
In this study, the radon gas concentration as well as the annual effective dose in leaves of the Malvasylvestris (Khabbaz) plant used in the traditional treatment and as food in Iraq, for this, it is necessary to evaluate the concentrations radon gas, which were measured using solid state nuclear track detectors (SSNTDs) CR-39 technique.  The  concentration and annual effective dose in samples were collected from Baghdad city ranged from minimum to maximum value 15.815 , 0.498 , 54.445 , 1.717  respectively, while the values of  concentration and annual effective dose in a sample collected from Karbala are 15.297 ,0.482 . These values of  concentration and annual effective dose less were compared with the samples from Baghdad.  The annual effective dose lies well within the safe limits as recommended by WHO.  So, the uses of Malvasylvestris plant are in traditional medicine and as a safe food for human consumption.